Identification of the GlialCAM interactome: the G protein-coupled receptors GPRC5B and GPR37L1 modulate megalencephalic leukoencephalopathy proteins. Issue 17 (7th June 2021) - Alonso-Gardón, Marta; Elorza-Vidal, Xabier; Castellanos, Aida; La Sala, Gina; Armand-Ugon, Mercedes; Gilbert, Alice; Di Pietro, Chiara; Pla-Casillanis, Adrià; Ciruela, Francisco; Gasull, Xavier; Nunes, Virginia; Martínez, Albert; et al.
Abstract: Megalencephalic Leukoencephalopathy with subcortical Cysts (MLC) is a type of vacuolating leukodystrophy, which is mainly caused by mutations in MLC1 or GLIALCAM . The two MLC-causing genes encode for membrane proteins of yet unknown function that have been linked to the regulation of different chloride channels such as the ClC-2 and VRAC. To gain insight into the role of MLC proteins, we have determined the brain GlialCAM interacting proteome. The proteome includes different transporters and ion channels known to be involved in the regulation of brain homeostasis, proteins related to adhesion or signaling as several G protein-coupled receptors (GPCRs), including the orphan GPRC5B and the proposed prosaposin receptor GPR37L1. Focusing on these two GPCRs, we could validate that they interact directly with MLC proteins. The inactivation of Gpr37l1 in mice upregulated MLC proteins without altering their localization. Conversely, a reduction of GPRC5B levels in primary astrocytes downregulated MLC proteins, leading to an impaired activation of ClC-2 and VRAC. The interaction between the GPCRs and MLC1 was dynamically regulated upon changes in the osmolarity or potassium concentration. We propose that GlialCAM and MLC1 associate with different integral membrane proteins modulating their functions and acting as a recruitment site for various signaling components as the GPCRs identified here. We hypothesized that the GlialCAM/MLC1 complex is working as an adhesion molecule coupled to a tetraspanin-like molecule performing regulatory effects through direct binding or influencing signal transduction events.